What's so funny about marketing? Twentieth-century cartoonist portrayals of US marketing. (20th February 2017) - Jorgensen, Brian K.
Abstract : Purpose: This purpose of this paper is to present an investigation into changes in portrayals of marketing by individuals outside of the industry during the important time frame between 1930 and 1999. The twentieth century was a period of significant development in how scholars and practitioners viewed the theory and activities of marketing. Design/methodology/approach: The study consisted of a content analysis of 1, 400 randomly selected marketing-related cartoons published in The New Yorker magazine from 1930 through 1999. Findings: The aspects of marketing portrayed by individuals outside of the discipline, specifically cartoonists, shifted over the early/mid to later parts of the twentieth century. In particular, earlier portrayals focused primarily on retail store transactions, while later portrayals depicted an increased incidence of marketing communications taking place outside the store setting. Eventually, more portrayals also addressed the adoption of marketing ideas and vocabulary into non-marketers' everyday lives. Overall, the proportion of portrayals that showed marketing in a negative light was low. Originality/value: This study investigates changes in portrayals of marketing by non-marketers over a seven-decade period of significant development of marketing thought. Both the relatively long period and the outsiders' perspective provide meaningful contributions. Also, findings do not support the perception that marketing and marketers are commonly viewed by those outside of marketing as unethical or likely to be in conflict with customers.